The recollections of Rifleman Harris a British soldier in the Napoleonic wars - Harris, Benjamin 1781-1858 (Dover Publications, Inc., 2019)
"Rare account of army life by common British foot soldier in early 1800s tells of camaraderie among infantrymen, physical hardships, endemic drunkenness, frequent hunger, and the narrow margin between death and survival."--
Includes index
"This Dover edition, first published in 2019, is an unabridged republication of a standard edition of The Recollections of Rifleman Harris, which was originally published in London in 1848. A new Publisher's Note has been specially prepared for this edition."
Keywords: Napoleonische Kriege; Soldat; Großbritannien; Harris, Benjamin / 1781-1858; Peninsular War, 1807-1814 / Personal narratives, British; Great Britain / Army / Light Infantry / 95th Regiment; Soldiers / Great Britain / Biography; Peninsular War (1807-1814); Soldiers; Great Britain; 1807-1814; Biography; Personal narratives / British; Erlebnisbericht